GEOCHEMICAL CHARACTERISATION OF SOILS AND SEDIMENTS FROM ONITSHA METROPOLIS, SOUTHEASTERN NIGERIA (2017)
Studies on the distribution, sources and impacts of Heavy Metals (HMs) and Polycyclic Aromatic Hydrocarbons (PAHs) in soils and sediments of Urbanised Industrialised Cities (UICs) are integral part of environmental monitoring programme globally. Results from such, have been used to design appropriate mechanisms for the sustainable use of environmental media. However, several Nigerian UICs, such as Onitsha, the most industrialized city Southeastern Nigeria, have not been adequately studied. Therefore, this study was designed to investigate the mineralogical, elemental and PAHs composition of soils and sediments in Onitsha metropolis in order to ascertain their sources, characters and potential mobility. One hundred and fourteen soils, 42 sediments and 6 rock units (geologic control) were purposively collected for the study. One sample each of galena, coal, soot from vehicle exhaust and used battery cells were also collected for Pb isotopes analysis for pollutant source characterisation. The mineral contents of the soils were determined using X-ray Diffractogram (XRD) technique. All the samples were digested and analysed for total elemental composition using Inductively Coupled Plasma-Mass Spectrometry (ICP-MS). Samples with the most elevated HMs (Pb, Zn, As, Mn, and Cd) were further subjected to sequential extraction and analysed with ICP-MS. The soils, sediments, galena, coal, soots from vehicle exhaust and used battery cells were analysed for lead isotopes, (Pb204, Pb206, Pb207 and Pb208) using ICP-MS. The concentrations of the PAHs were determined using Gas Chromatography/Mass Spectrometry (GC/MS). Data were analysed using descriptive and inferential statistics. Quartz, kaolinites and hematite were the dominant minerals present in the soils. The selected HMs concentrations (mg/kg) in soils, sediments and rock units revealed that Pb ranged from 7.2-2026.0, 19.7-540.1 and 7.2-28.1; Zn, 3.0-8395.0, 101.1-502.5 and 3.0-35.3; As, 0.5-19.8, 80.6-16.9 and 0.5-27.3; Mn, 7.1-1920; 180-1410 and 10.0-221.0; Cd, 0.1-1.03, 0.21-1.6 and < 0.01, below detection limits, respectively. Soils and sediments showed higher concentrations for Pb, Zn, Cd and Mn than the rock units except for As. The sequential extraction showed that Zn and Cd were more in the carbonate bound fraction, while As was higher in the Organic bound fraction with Mn and Pb more in the hydroxide and residual fractions, respectively. The estimated mobility of HMs was Cd>Zn>As>Mn>Pb. The standard plots of 206Pb/204Pb vs 207Pb/204pb and 207Pb/204Pb vs 206Pb/204Pb in the soils and sediments, respectively exhibited linear relationship suggesting similar origin of Pb in the environmental media. The PAHs mean concentrations (µg/g) were: Fluoranthene, 187.2 ± 146.4, Pyrene, 187.5 ± 133.7, Benzo[a]anthracene, 93.8 ± 72.0, 150.4 ±94.8 and Benzo[a]pyrene, 178.9 ± 112.2, respectively. The standard plots of the ratios of the Anthracene: (Anthracene + Phenanthrene) and Fluranthene: (Fluranthene + Pyrene), indicated that the PAHs were from Pyrogenic (combustion) activities. The heavy metals and high molecular weight Polycyclic Aromatic Hydrocarbons in the soils and sediments of Onitsha were of anthropogenic sources except for arsenic that had a substantial geogenic input. Mobility of the HMs were also established.